Bone tumors distribution in diagnostic and excisional biopsies - Almigdad, Ahmad Khaled; Dagher, Bara’ Zaid; Alwaqfi, Ola Mohammad; Ghabashneh, Mutaz Ahmad; Alfqaha, Hamzeh Ahmad (Journal of Musculoskeletal Surgery and Research)
Objectives: Bone tumors are uncommon. Nevertheless, bone is a common site for metastasis. Due to limited data regarding bone tumors in Jordan, this study aims to understand better bone tumor epidemiology and distribution in the Jordanian population. Methods: A part of a retrospective, single-center study, all biopsy reports confirming the diagnosis of a bone tumor between January 2017 and December 2019 were abstracted from Princess Iman Research Center records. The patients’ age, gender, anatomical location, and histopathological type of the tumors were obtained and analyzed. Results: Two hundred eighty-four diagnostic and excisional biopsies were reviewed. Most of the patients (60.2%) were males. The mean age for the patients was 26.74(±16.29) years. Malignant bone tumors were diagnosed in 15.5%. The femur was the most common site of biopsy diagnosed tumor followed by the tibia. Osteochondroma was the most commonly diagnosed benign tumor and accounted for 39.4%, followed by aneurysmal bone cysts (14.8%), and enchondroma (10.2%). The metastatic bone tumors were the most frequent malignant bone pathology (6.7%), while osteosarcoma was the most common primary sarcoma, diagnosed in 5.6% of the sample. Increasing age, pelvic, and spine location of bone tumors were found to be significantly associated with malignancy. Conclusion: In our 284 samples, osteochondromas were the most commonly diagnosed tumors (39.4%), followed by aneurysmal bone cysts (14.8%), and enchondromas (10.2%). Metastatic tumors were the most common malignant bone pathologies, while osteosarcomas were the most common primary bone sarcomas. Femur and tibia were the most common tumor-located sites. Breast and lung deposition were the most common metastasis primaries. Additionally, increasing age, pelvic, and spine-located bone tumors were significantly associated with malignancy.